(1) If f(x) = a^x, show that f(A + B) = f(A) * f(B) (2) If f(x) = a^x, show that f(Ax) = [f(x)]^A
Follow Math Help Forum on Facebook and Google+
Originally Posted by magentarita (1) If f(x) = a^x, show that f(A + B) = f(A) * f(B) (2) If f(x) = a^x, show that f(Ax) = [f(x)]^A f(x) = a^x f(A + B)=a^(A + B) =a^A*a^B but a^A =f(A) and a^B=f(B) putting these values we get f(A + B) = f(A) * f(B) hence proved 2)f(x) = a^x f(Ax) =a^(Ax) =(a^x)^A =[f(x)]^A therfor f(Ax) =[f(x)]^A hence proved
(1) (2)
Wonderfully done!
View Tag Cloud